Respuestas

  • Usuario de Brainly
2013-05-23T04:25:04+02:00
(8 - 3x) 4 (2 +3x) = 12
(8 - 3x) (8 + 12x) = 12
64 + 96x - 24x - 36x² = 12         igualamos a cero
64 + 72x - 36x² - 12 = 0

- 36x² + 72x + 52 = 0

aplicamos Bascara
        –b ± √ b² – 4ac
x = ▬▬▬▬▬▬▬                  donde a = - 36  b= 72      c= 52
              2a


      –72 ± √5184 – 4(-36)(52)
x = ▬▬▬▬▬▬▬
▬▬▬▬▬▬
              2( - 36)

      –72 ± √5184 + 7488
x = ▬▬▬▬▬▬▬
▬▬▬▬▬▬
             - 72


     –72 ± √12672
x = ▬▬▬▬▬▬▬

             - 72


     –72 ± 112,56
x = ▬▬▬▬▬▬▬

             - 72


x1 = (- 72 + 112,56)/ -72 → x1 = 0,5633.....
x2= (-72 - 112,56) / -72 → x2=  2.5633...

espero que te sirva, salu2!!!!!